Evaluation of protective coating and inert surfaces adhesion - Vergun, L.Yu.; Zabashta, Yu.F.; Todosiychuk, T.T.; Kosyanchuk, L.F.; Zagorodnia, O.A. (Functional Materials, 2014)
The physical mechanisms of interaction between the substrate and the inert polymeric material have been studied. It has been showed that during such interaction the structures of oriented chains are formed. While the bounds are breaking in these areas the strands which can attributed to structural features called "silver cracks" occur.